Nb-containing micro-alloyed high-carbon steel hot-rolled wire rod and manufacturing method thereof - ZHOU DE; WANG QUANLI; LI YONGDONG; ZHU YINXIANG; YE SHAOFENG; DING NING; CHENG SIHUA; SUN QISONG; SHI CHANG; LI SANKAI; ZHANG YONGQING; KONG XIANGTAO (2013)
The invention comprises an Nb-containing micro-alloyed high-carbon steel hot-rolled wire rod and a manufacturing method thereof. The invention belongs to the technical field of hot-rolled wire rods. The hot-rolled wire rod comprises the components of, by mass: 0.83-1.00% of C, 0.15-0.35% of Si, 0.6-0.9% of Mn, 0-0.50% of Cr, 0-0.15% of V, 0.01-0.20% of Nb, and balance of Fe. A converter is adopted; a double slag method is adopted; and high tensile carbon operation is adopted. Slag is blocked, and molten steel is tapped. Recarburization is carried out by using a low-nitrogen recarburizer. When steel is fetched from an LF refining station, an oxygen activity is controlled below 10ppm. In a refining final slag, a total amount of FeO and MnO is no higher than 3%. An inclusion modification treatment is carried out on a Ca-Si line. 160mm*160mm small billets are adopted. Terminal electromagnetic stirring is adopted in cooperation of a crystallizer. Full-protection and constant-pulling-speed casting is carried out by